Żaby w Biblii na tle innych antycznych tradycji - Laskowski, Łukasz (Verbum Vitae, 2017)
The article considers the presence of frogs in the Bible (16 occurrences) in relation to the wider symbolic meaning of this creature in antiquity. The ancient symbolism of frogs enables us to notice both the similarities and the differences between the biblical texts of the Israelites/Jews and the cultures of neighboring peoples. In the narrative of Exodus, frogs are the agents of divine punishment. In the Septuagint frogs are associated with the action of God, probably as a result of their relation to magic. The Old Testament interprets the second plague in the context of prayer. In the New Testament, frogs are found only in the Book of Revelation. The context of their appearance has a demonological and magic nature; frogs, as unclean animals, are symbols of evil spirits and their influence.